Role of hippocampal volumetry in drug resistant epilepsy - Sachdev, Namrita; Gupta, Shivani; Singh, Yashvant (International Journal of Research in Medical Sciences, 2019)
Background: Hippocampus is a brain structure located deep in the temporal lobe. The structure is crucial for learning and memory and is a natural inhibitor of seizure activity in brain. In drug resistant epilepsy (DRE), there is shrinkage of the hippocampus leading to poor seizure control. Methods: Patients meeting the diagnostic criteria for drug resistant epilepsy between the age group of 10-60 years were enrolled in the study. Epileptic non drug resistant controls and normal healthy individuals were taken from same cohort. Selected patients underwent MRI Brain and their hippocampal volumes were estimated manually. Coronal oblique sections, perpendicular to the long axis of hippocampus were taken and hippocampal volume (HV) were calculated using region of interest approach with manual delineation . Results: There was increment in detecting hippocampal atrophy from 30% to 46.6% in DRE patients when manual hippocampal atrophy was used in addition to visual assessment. The mean right and left hippocampal volumes in drug resistant epilepsy cases were found to be 2.17+0.57 cc and 1.52+0.54 cc respectively. Left HV was found to be statistically significantly smaller than right side (p value < 0.05). DRE patients had smaller mean bilateral HV than healthy controls, the difference being 33%. The left HV loss was almost double the right HV loss among DRE cases. The hippocampal volumes were reduced in DRE patients compared to epileptic non-resistant patients; however the difference was found to be less than that of normal healthy controls. Conclusion: Manual hippocampal volumetry detected more patients with hippocampal atrophy in our study compared to visual assessment. Manual hippocampal volumetry should be routinely done in patients with Drug resistant epilepsy.